KEPERCAYAAN SEBAGAI PEMEDIASI PENGARUH KUALITAS PELAYANAN TERHADAP NIAT MEMBELI KEMBALI PADA PENGGUNA SHOPEE DI KOTA DENPASAR - Wiwekananda, Ida Bagus; Suasana, I Gst. A. Kt. Gd. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.08.TAHUN.2023, 2023)
Shopee utilizes digital services through applications to respond to changes in people's behavior. Shopee must carry out the right service & strategy so that consumers feel comfortable and trust so that they have the intention to buy back at Shopee. The purpose of this study was to explain the effect of service quality on repurchase intentions, the effect of service quality on trust, the effect of trust on repurchase intentions and the role of trust as a mediator of the effect of service quality on repurchase intentions. This research was conducted in Denpasar City. Samples were taken as many as 142 respondents through purposive sampling method and distributed using a google form questionnaire with adjusted criteria. Measured by 17 indicators and using a Likert scale. The data analysis technique used is path analysis and sobel test. The results of this study indicate that all hypotheses are accepted. Service quality has a positive and significant effect on repurchase intentions, service quality has a positive and significant effect on trust, trust has a positive and significant effect on repurchase intentions and trust plays a significant role in mediating the effect of service quality on repurchase intentions.